2020
DOI: 10.1101/2020.08.15.252510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid cost-effective viral genome sequencing by V-seq

Abstract: Conventional methods for viral genome sequencing largely use metatranscriptomic approaches or, alternatively, enrich for viral genomes by amplicon sequencing with virus-specific PCR or hybridization-based capture. These existing methods are costly, require extensive sample handling time, and have limited throughput. Here, we describe V-seq, an inexpensive, fast, and scalable method that performs targeted viral genome sequencing by multiplexing virus-specific primers at the cDNA synthesis step. We designed dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The next aspect we evaluated was when to add the DNA indices that distinguish individual samples. These can in principle be incorporated during the RT 15,18,19 as well as during the PCR 24,25 , as extensions of the primers used to reverse transcribe or amplify the desired amplicons, respectively (Fig. 1C) .…”
Section: Methods Development and Resultsmentioning
confidence: 99%
“…The next aspect we evaluated was when to add the DNA indices that distinguish individual samples. These can in principle be incorporated during the RT 15,18,19 as well as during the PCR 24,25 , as extensions of the primers used to reverse transcribe or amplify the desired amplicons, respectively (Fig. 1C) .…”
Section: Methods Development and Resultsmentioning
confidence: 99%
“…We recently developed V-seq, a sequencing method that uses virus-specific RT primers tiled across the SARS-CoV-2 genome for viral sequence enrichment (Guo et al, 2020). The V-seq protocol is more rapid and 10 times cheaper than commercially available meta-transcriptomics approaches ( e.g ., NEBNext Ultra II).…”
Section: Resultsmentioning
confidence: 99%
“…For reads assigned to primer set oP2, we combined the 8 base-pair UMI with the 6 base-pair random hexamer to create a 14 base-pair UMI. For a more detailed description of the primer design see (Guo et al, 2020). We used the GroupReadsByUmi tool from the fgbio (v1.2.0; https://github.com/fulcrum-genomics/fgbio) toolkit to group reads using this UMI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reads mapping to viral sequences in samples containing no SARS-CoV-2 RNA are a source of false positive test outcomes and limit sensitivity of detection assays. Non-zero background has been observed in other sequencing-based assays for SARS-CoV-2 detection 23,24,53 , and molecular contamination and mis-assignment of sequencing reads were identified as main underlying sources 23 . Leveraging the UMI information we have shown that between 1% and 6% of the UMI counts in a pool are contaminants of another pool (Figure S7B), resulting from events taking place after reverse transcription (during library amplification or sequencing).…”
Section: Sources Of and Strategies To Improve Incomplete Umimentioning
confidence: 99%